EFFECT OF GEL FORMULATION CONTAINING Tridax procumbens AND Aloe vera LEAF EXTRACT ON THE HEALING OF SECOND-DEGREE BURNS IN MICE (Mus musculus) - Maturbongs, Marsela; Setyawati, Iriani; Manampiring, Nonny; Lawalata, Helen; Taulu, Marthy; Rompas, Christny (Universitas Negeri Manado, 2025)
Tridax procumbens L. and Aloe vera L. are plants commonly used in the treatment of burns. This study was conducted to determine the effect of giving a combination gel of T. procumbens and A. vera leaf extract on second-degree burn healing in mice. This study used 24 male mice (Mus musculus) which were divided into four treatment groups, namely positive control (KP, Bioplacenton®); negative control (KN, gel base); leaf extract of T. procumbens 0.5% and A. vera 0.5% (P1); and leaf extract of T. procumbens 1% and A. vera 0.5% (P2). The process of inducing burns on the backs of mice requires the use of a 1x1 cm iron, which is subjected to heat in a fire for three minutes. The iron is placed on the mice's back for five seconds, which leads to the development of a second-degree burn. The gel was applied twice a day for 21 days. The highest level of burn wound healing was recorded with the Bioplacenton® treatment, which achieved a full recovery of 100% on day 15. Following this, the combined gel treatment of 1% T. procumbens leaf extract and 0.5% A. vera also reached 100% healing by day 18. While it may not be as potent as Bioplacenton®, the gel formulation containing 1% T. procumbens and 0.5% A. vera leaf extract presents a viable alternative for treating second-degree burns.